(untitled) (International Seven Journal of Health Research, 2025)
Autism Spectrum Disorder (ASD) is characterized by cognitive impairment and impairment in behavioral and social interaction. Of complex etiology, considering interactions between genetic and epigenetic factors. Objective: The research proposes to investigate the genetic contribution underlying Autism Spectrum Disorder (ASD). Methods: A systematic literature review methodology is used in the PubMed, Scientific Electronic Library Online (Scielo) and VHL databases via DeCS/MeSH descriptors in any language. Results and discussions: The findings highlight the strong predominance of genetic influences in ASD, evidencing the alteration of more than 800 documented genes, whose heritability is greater than 80%. Covering a diverse plexus regarding its functionality with changes in chromatin remodeling, transcription factors/regulators, mRNA traffic regulators, protein modification, cell proliferation, and synaptic architecture. Genomic interactions that include deletion, translocation, polymorphism and specific mutations found in the genes: MTHFR, GABRB3, RELN, OXTR, RTTN, SOCS6, CBLN2, and the alteration of the chromosomal chromosomes in the numbers :1, 2, 3, 7, 16, 22, with a predominance of 17, were highlighted. Responsible for altering the formation of proteins and neurotransmitters indispensable for the development of physical, social and behavioral skills. In addition, association with RETT and X-fragile syndromes. Conclusion: Therefore, this research highlights the genetic complexity of ASD with a high degree of heritability, the insufficiency of genetic testing, reliable biological markers, and the pressing need for additional advances in diagnosis, clinical management, and early therapeutic approaches.